2013
DOI: 10.1021/pr300755p
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Proteomics Approach in Characterizing and Quantifying Allergenic Proteins from Northern Shrimp: Toward Better Occupational Asthma Prevention

Abstract: Occupational asthma is a major chronic health dilemma among workers involved in the seafood industry. Several proteins notoriously known to cause asthma have been reported in different seafood. This work involves the application of an allergenomics strategy to study the most potent allergens of northern shrimp. The proteins were extracted from shrimp tissue and profiled by gel electrophoresis. Allergenic proteins were identified based on their reactivity to patient sera and were structurally identified using t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 49 publications
(20 citation statements)
references
References 36 publications
0
20
0
Order By: Relevance
“…Interestingly, after heat treatment, AK IgE reactivity was reduced to just one AK variant at 36.5 kDa. We recently demonstrated that the heat‐stable novel AK from northern shrimp can be aerosolized and cause inhalational sensitization in the workplace .…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, after heat treatment, AK IgE reactivity was reduced to just one AK variant at 36.5 kDa. We recently demonstrated that the heat‐stable novel AK from northern shrimp can be aerosolized and cause inhalational sensitization in the workplace .…”
Section: Discussionmentioning
confidence: 99%
“…Grinded insects were defatted with diethyl ether following the method proposed by Caligiani et al 31 using a Soxhlet extractor (SER 148/3 VELP SCIENTIFICA, Usmate Velate, Italy). Defatted flours were subjected to the protein extraction protocol proposed by Abdel Rahman et al 32 with some modifications. Briefly, 0.5 g of sample were homogenized in an ice-bath with 10 mL of a Tris buffer (25 mM Tris-HCl pH 8.0, 1 M KCl, 50 mM DTT and 0.5 mM EDTA) using Ultra Turrax homogenizer (11000 rpm) for 1 minute.…”
Section: Methodsmentioning
confidence: 99%
“…Troponin C (TpC) was first described as an allergen in Crangon crangon (Cra c 6, North Sea shrimp) , recognized by 9/31 (29%) of the patients, and later in Pandalus borealis (northern shrimp), recognized by 33% of the patients . In a recent study by Pascal et al , sensitization to TpC was found in 17.2% of 58 shrimp‐allergic patients.…”
Section: Allergensmentioning
confidence: 99%
“…During the last two decades, significant progress in biochemistry and molecular biology enabled the characterization, cloning, and recombinant production of various shellfish allergen components and epitope‐emulating peptides that might become available for quantification of specific IgE (sIgE) antibodies, namely molecular diagnosis. This review intends to summarize our current knowledge about shellfish allergens and their cross‐reactivity as this might be the key to optimize diagnosis .…”
mentioning
confidence: 99%